A Shift in the Security Paradigm
XXVIII, 271 p. 17 illus., 15 illus. in color.
Keywords: This book discusses some of the strategic lines in front of the trends related to the new challenges of global security in this new century: some rather universal problems (migration, terrorism, cyberspace, conflict resolutions techniques in prisons, economic intelligence), as well as more military ones (new conflicts: new world stage, new weapons, new military doctrines, mass destruction weapons and nuclear arms control, outer space and ocean depths), without forgetting some global and conceptual topics (disintegration is driving insecurity, searching for quality in international affairs, shield of security culture through data protection, information society and the protective influence of security culture). A special focus is put on Europe's interests. The unique, complex process of integration of European states is confronted by various problems caused by the implementation of different political visions presented by the factions of the European Union'sestablishment. The diverse interpretation of the goals and paths of development of this organization leads to the violation of its cohesion, which is used by global partners with the opportunity to broaden their influence and achieve their own goals by playing European countries individually. There is a need for the EU to go further to achieve a deeper level of integration and strategic autonomy which would allow for the implementation of a coherent policy towards the powers.